2019
DOI: 10.1002/lt.25322
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Nonmalignant Portal Vein Thrombosis in Transplant Recipients With Nonalcoholic Steatohepatitis

Abstract: Nonalcoholic fatty liver disease (NAFLD) is an increasingly prevalent condition and its more severe progressive state, nonalcoholic steatohepatitis (NASH), is currently the second most common indication for waitlisted adults in the United States. The association of portal vein thrombosis (PVT) prior to or at transplant and poor graft and patient outcomes is not well established, particularly among NASH patients who inherently have an increased hypercoagulable profile. Using the United Network for Organ Sharing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 30 publications
1
26
0
Order By: Relevance
“…PVT is a common complication in liver transplant candidates that is strongly associated with inferior outcomes in the perioperative transplant setting, including increased morbidity and mortality, which parallel lower health‐related quality of life . Consequently, the decision to proceed with liver transplantation listing, surveillance imaging, and treatment with either anticoagulation or transjugular intrahepatic portosystemic shunt (TIPS) in transplantation candidates with PVT remains one of much debate and uncertainty.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…PVT is a common complication in liver transplant candidates that is strongly associated with inferior outcomes in the perioperative transplant setting, including increased morbidity and mortality, which parallel lower health‐related quality of life . Consequently, the decision to proceed with liver transplantation listing, surveillance imaging, and treatment with either anticoagulation or transjugular intrahepatic portosystemic shunt (TIPS) in transplantation candidates with PVT remains one of much debate and uncertainty.…”
Section: Discussionmentioning
confidence: 99%
“…This is increasingly important given the worsening obesity and NASH epidemics that parallel the increasing demand for liver transplantation as evidenced by the fact that NASH is the leading indication for liver transplantation in women and simultaneous liver‐kidney transplantation for all sexes . Perhaps more importantly, recipients with NASH and PVT have inferior posttransplantation survival as demonstrated by Agbim et al, who found a 37% increased risk of graft failure and a 31% increased risk of overall death in NASH transplant recipients with PVT compared with NASH recipients without PVT at transplant. As more and more patients develop NASH cirrhosis, we would expect an increasing number of high‐risk patients to be identified by the PVT‐RI, further increasing its future clinical utility.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because the authors did not know if the presence of moderate‐to‐severe ascites predated the PVT, the data may show that more severe portal hypertension either predisposes patients to PVT or results from PVT; both are plausible but not distinguished in this study. In addition, NASH has previously been shown to be an independent risk factor for PVT in the UNOS data set, which is believed to be increased secondary to obesity and chronic inflammation . However, more work is needed to further detail the specific reasons for this finding.…”
mentioning
confidence: 99%